2021
DOI: 10.1177/1420326x211030323
|View full text |Cite
|
Sign up to set email alerts
|

Indoor thermal climate after energy efficiency measures of a residential building in a sub-Arctic region: Comparing ANSYS CFX and IDA ICE methods

Abstract: A residential building which had been subjected to an energy efficiency measures study had its indoor thermal climate investigated using two software approaches to understand how each approach would predict the outcome, using the predicted percentage of dissatisfied (PPD). The computational fluid dynamics software (ANSYS CFX) and the building performance simulation (BPS) software (IDA ICE) were used to simulate the indoor thermal climate before and after the measures. The measures included additional insulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(55 reference statements)
0
1
1
Order By: Relevance
“…67 The choice of modelling tool and/or algorithm can lead to different estimates of indoor temperatures, and building performance models may give a less accurate estimate than computational fluid dynamics, for example. 68,69 Other studies have noted that the overheating metric selected may influence the relative risks of overheating across dwelling variants, 66 however in this study we found a reasonable association between CDH and maximum indoor temperature.…”
Section: Discussioncontrasting
confidence: 43%
“…67 The choice of modelling tool and/or algorithm can lead to different estimates of indoor temperatures, and building performance models may give a less accurate estimate than computational fluid dynamics, for example. 68,69 Other studies have noted that the overheating metric selected may influence the relative risks of overheating across dwelling variants, 66 however in this study we found a reasonable association between CDH and maximum indoor temperature.…”
Section: Discussioncontrasting
confidence: 43%
“…As an effective method for simulation, [36][37][38][39][40][41] CFD was widely employed in the simulation of airflow field, pollutant (e.g. PM 2.5 ) field and thermal field.…”
Section: Numerical Simulationsmentioning
confidence: 99%